Cerebroventricular Microinjections of MPTP on Adult Zebrafish Induces Dopaminergic Neuronal Death, Mitochondrial Fragmentation, and Sensorimotor Impairments - Kalyn, Michael; Ekker, Marc (Frontiers in Neuroscience, 2021)
Mitochondria are dynamic organelles that mediate the energetic supply to cells and mitigate oxidative stress through the intricate balance of fission and fusion. Mitochondrial dysfunction is a prominent feature within Parkinson Disease (PD) aetiologies. To date, there have been conflicting studies of neurotoxin impact on dopaminergic cell death, mitochondrial function and behavioral impairment using adult zebrafish. Here, we performed cerebroventricular microinjections of MPTP on adult transgenic zebrafish that resulted in significant reductions in dopaminergic neurons within the telencephalon and olfactory bulbs of Tg(dat:eGFP) fish. Visualization of mCherry and mitochondrial gene expression analysis in Tg(dat:tom20 MLS:mCherry) fish reveal that MPTP induces mitochondrial fragmentation in dopaminergic neurons and the activation of the pink1/parkin pathway involved mitophagy. Moreover, the loss of dopaminergic neurons translated into a transient locomotor and olfactory phenotype. Taken together, these data can contribute to a better understanding of the mitochondrial impact on dopaminergic survivability.